The Influence of Symbolic and Hedonic Value on Customer Engagement with Trust as an Intervening Variable for Gen Z Consumers of Eiger Products via Shopee Live-Streaming in Malang City - Maya Aulia Ilma; Amelindha Vania (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to examine the impact of symbolic and hedonic value on customer engagement through trust in Gen Z consumers of Eiger products via Shopee live streaming. Eiger product sales have increased by 16 times thanks to Shopee live streaming, which allows buyers to see the seller in real-time and interact with them. This study's method is descriptive quantitative, with data analyzed using PLS-SEM and SmartPLS 3.0. The study's findings indicate that trust can fully mediate between symbolic value and customer engagement, while trust can only partially mediate between hedonic value and customer engagement among Gen Z consumers purchasing Eiger products through Shopee live streaming.